Qualitative Study: The Role of Traditional Bejah and Poultice Practices in Uterine Recovery in Postpartum Mothers - Yuniantini, Ummy (PSPP JOURNALS, 2025)
Background the postpartum period includes a critical transition period for mothers and babies physiologically, emotionally, and socially. According to data from the World Health Organization (WHO) in 2019, maternal mortality rates are very high, every day around 810 women die from preventable causes related to pregnancy and childbirth. The purpose of this study was to determine the effectiveness of the use of bejah and poultice on the process of uterine involution in postpartum mothers in Pontianak. The research method used a qualitative approach with a phenomenological study design. This approach was chosen to explore in depth the experiences, perceptions, and meanings felt by postpartum mothers regarding the use of bejah and poultice. Research Results Bejah and poultice are common health treatments carried out by postpartum mothers among Malay people in Pontianak. Bejah is considered a traditional antibiotic to speed up the healing of birth canal wounds. Poultice is ash from burning wood or coconut mixed with tamarind and other spices. Poultice is applied on the stomach, under the octopus. Conclusion Overall, the practice of bejah and poultice in Pontianak can be seen as a traditional approach that has the potential to support the process of uterine involution psychologically and culturally.